2016
DOI: 10.2147/rru.s120748
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of biochemical recurrence in patients with high-risk prostate cancer treated with radical prostatectomy and radiotherapy plus androgen deprivation therapy

Abstract: ObjectiveThe aim of this study was to evaluate the biochemical recurrence (BCR) in patients with high-risk prostate cancer (PCa) treated with radical prostatectomy (RP) or radiotherapy (RT) plus androgen deprivation therapy (ADT).MethodsSubjects were patients with National Comprehensive Cancer Network-defined high-risk PCa treated with either RP or RT plus ADT. We calculated BCR-free survival in patients with those treatments and evaluated risk factor against BCR.ResultsA total of 114 patients, 71 RP and 43 RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Ten studies 15 16 17 19 21 22 24 25 27 28 provided data of EBRT modality, such as conventional EBRT, three dimensional conformal radiation therapy, and intensity modulated radiation therapy. Radiation dosage was only mentioned in 15 15 16 17 18 19 20 21 22 23 24 25 27 28 29 31 of 17 studies and mostly ranged from 60 to 80 gray (Gy, J kg −1 ). In addition, considerable variability was found in the use of adjuvant or salvage therapies, regardless of the modality or duration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies 15 16 17 19 21 22 24 25 27 28 provided data of EBRT modality, such as conventional EBRT, three dimensional conformal radiation therapy, and intensity modulated radiation therapy. Radiation dosage was only mentioned in 15 15 16 17 18 19 20 21 22 23 24 25 27 28 29 31 of 17 studies and mostly ranged from 60 to 80 gray (Gy, J kg −1 ). In addition, considerable variability was found in the use of adjuvant or salvage therapies, regardless of the modality or duration.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 17 studies included, 16 were retrospective 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 and one was a RCT. 15 The RCT scored three out of five points (considered as high quality) according to the Jadad Scale.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 12 studies, patients of four cohorts [ 11 14 ] were treated with 3DCRT or RP, three studies [ 4 , 15 , 16 ] provided eligible data limited to IMRT, and other articles [ 17 21 ] contained both 3DCRT and IMRT. The radiation dose ranged from 70 Gy to 86.4 Gy, and patients treated with EBRT were mostly older than those who received RP.…”
Section: Resultsmentioning
confidence: 99%
“…Treatment-related toxicity should also be assessed. Among the included articles, two studies [ 15 , 21 ] reported the adverse events of EBRT, which mostly consisted of diarrhea, anal pain and urinary frequency. Another studies [ 13 ] compared the health-related quality of life and functional outcomes of patients treated with RP or EBRT.…”
Section: Discussionmentioning
confidence: 99%